Impact of a low-cost bundle of interventions on infection prevention and control during labour and delivery in rural health centres in Zambia: results from a quasi-experimental study - Park, Jason H.; Mwananyanda, Lawrence; Bwalya, Misheck; Coffin, Susan E.; MacLeod, William B.; Hamer, Davidson H. (International Journal of Infection Control, 2023)
Infection remains an important cause of maternal and newborn morbidity and mortality globally despite evidence that it can be reduced with adherence to infection prevention and control (IPC) practices. The implementation of IPC has been especially challenging in rural health centres. This pilot study used a non-randomised quasi-experimental design to examine the impact of a low-cost intervention bundle at five rural health facilities in Southern Province of Zambia. We used the Infection Control Assessment Tool (ICAT) and surveyed the incharge nurse, observed deliveries and reviewed logbooks to collect pre- and post-intervention data on healthcare worker IPC practices and maternal and newborn outcomes. The intervention bundle included education sessions, provision of alcohol hand rubs (AHRs), short message service (SMS) text messages and poster reminders, and monthly study visits. The overall ICAT score did not significantly increase after the intervention (64.0 vs. 71.8, maximum score 133, P = 0.28). There was a significant increase in the labour and delivery practices module score (12.5 vs. 16.6, maximum score 27, P = 0.04) and a trend towards improvement in the hand hygiene module (9.1 vs. 13.6, maximum score 23, P = 0.08). There were no differences in pre- or post-intervention outcomes amongst the 654 mothers who delivered and the 655 newborns during the study period. In conclusion, a low-cost bundle of interventions did neither overall improve healthcare workers’ IPC practices in rural Zambia nor significantly change the rates of newborn and maternal complications. Identified challenges included inconsistent supplies of AHRs, protective and sterile equipment, as well as heavy workload for healthcare workers, which inhibited preventative behaviours.